2008
DOI: 10.1007/s10562-008-9646-7
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Protocol for Aza-Michael Addition Reactions Under Solvent-Free Condition Employing Sulfated Zirconia Catalyst

Abstract: The aza-Michael addition reactions of amines with a,b-unsaturated carbonyl compounds were efficiently carried out at room temperature under solvent-free condition employing sulfated zirconia as a reusable heterogeneous catalyst. The desired products were formed in short reaction times and in high yields. The bulk and surface properties of the synthesized catalyst was examined by X-ray powder diffraction, BET surface area, temperature programmed desorption of ammonia, scanning electron microscopy and thermograv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…Contrastingly, catalysts are often used for aza-Michael additions when synthesizing drug molecules, allowing lower activation energies and thus increased rates of reaction. Example catalysts include boric acid (Chaudhuri et al, 2005), lipases (Dhake et al, 2010), sulfonated zirconia (Reddy et al, 2008), copper(II) acetylacetonate (Kantam et al, 2005), and indium trichloride (Yang et al, 2007) but more commonly observed is the use of lanthanide metal-centered catalysts (e.g., SmI 2 Reboule et al, 2005 and Yb(OTf) 2 Jenner, 1995). Such catalysts have been shown to be particularly efficient for promoting aza-Michael additions, their activity assumed to be a result of Lewis acid behavior drawing electron density away from the C=C and making the β-position more susceptible to attack from the nucleophilic amine.…”
Section: Resultsmentioning
confidence: 99%
“…Contrastingly, catalysts are often used for aza-Michael additions when synthesizing drug molecules, allowing lower activation energies and thus increased rates of reaction. Example catalysts include boric acid (Chaudhuri et al, 2005), lipases (Dhake et al, 2010), sulfonated zirconia (Reddy et al, 2008), copper(II) acetylacetonate (Kantam et al, 2005), and indium trichloride (Yang et al, 2007) but more commonly observed is the use of lanthanide metal-centered catalysts (e.g., SmI 2 Reboule et al, 2005 and Yb(OTf) 2 Jenner, 1995). Such catalysts have been shown to be particularly efficient for promoting aza-Michael additions, their activity assumed to be a result of Lewis acid behavior drawing electron density away from the C=C and making the β-position more susceptible to attack from the nucleophilic amine.…”
Section: Resultsmentioning
confidence: 99%
“…It has been realized in recent years that sulfuric acid adsorbed on silica gel could be used as a multipurpose acid catalyst [27][28][29][30][31]. In continuation of our work on the development of useful synthetic methodologies by employing solid acid catalysts [32][33][34][35], we observed that H 2 SO 4 /silica *Address correspondence to this author at the Inorganic and Physical Chemistry Division, Indian Institute of Chemical Technology, Uppal Road, Hyderabad -500 607, India; E-mails: bmreddy@iict.res.in, mreddyb@yahoo.com gel is an efficient catalyst for the synthesis of coumarins via Pechmann condensation. In this communication, we are disclosing our findings on H 2 SO 4 /silica gel catalyzed Pechmann condensation of a series of phenols and -keto esters to coumarins under solvent free conditions.…”
Section: Introductionmentioning
confidence: 82%
“…Zeolites are natural (volcanic rock) or synthetic materials [1]. There are about fty natural zeolites and more than 150 synthetic zeolites [2]. The activity and the selectivity of the catalyst are in uenced by the characteristics of the catalyst when these characteristics depend on the method of preparation [3].…”
Section: Introductionmentioning
confidence: 99%